2020
DOI: 10.1590/0102-311x00136419
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of localized cutaneous leishmaniasis on adult patients of a referral service in Belo Horizonte, Minas Gerais State, Brazil

Abstract: Cutaneous leishmaniasis (CL) is a disease associated with low-income populations. Thus, in assessing the burden of this disease, it is important to include its economic impact on individuals. We aimed to evaluate CL economic impact on patients treated at a referral service in the State of Minas Gerais, Brazil. This is a cross-sectional study based on the analysis of interviews and medical records from which we assembled direct medical and non-medical costs related to CL, from a societal perspective. One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“… 147 In Brazil, 50% of study participants paid an average of 22% of their household income for CL-related costs. 148 In Bangladesh, the median total household cost per patient for PKDL treatment was $367, which was more than twice the per capita annual income of the studied population. 19 …”
Section: Socioeconomic Impacts Of the Leishmaniasesmentioning
confidence: 93%
See 3 more Smart Citations
“… 147 In Brazil, 50% of study participants paid an average of 22% of their household income for CL-related costs. 148 In Bangladesh, the median total household cost per patient for PKDL treatment was $367, which was more than twice the per capita annual income of the studied population. 19 …”
Section: Socioeconomic Impacts Of the Leishmaniasesmentioning
confidence: 93%
“…A 2017 cross-sectional study in Brazil found the total medical costs to CL patients was $125. 148 Top contributors to direct medical costs included medications (17%), medical appointments (15%), medical exams (9%) and health insurance costs (10%). Top contributors to direct non-medical costs were transportation to health centers (26%) and food (8%).…”
Section: Socioeconomic Impacts Of the Leishmaniasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Galvão et al 18 evaluated direct medical and non-medical costs related to CL treatment in a Brazilian referral center. One hundred patients were included; 50% had a monthly per capita income of up to USD 259.60 and spent on average USD 187.32 with the disease, representing an average monthly impact of 22.5% (USD 133.80).…”
Section: Economic Analysis Of Treatmentmentioning
confidence: 99%